029. Comorbidities’ burden in newly diagnosed obstructive sleep apnea patients - Xanthoudaki, Maria (J Thorac Dis, 2015)
BACKGROUND: Obstructive sleep apnea (OSA) is frequently associated with several comorbidities. OBJECTIVE: The study was to examine the characteristics and to evaluate gender differences in comorbidities in OSA patients. METHODS: The characteristics of 689 consecutive individuals (511 males and 178 females) evaluated with polysomnography due to suspected OSA were analyzed. Patients were divided according to OSA severity into three groups and comparisons were made between male and female patients. RESULTS: Mild OSA was diagnosed in 142, moderate in 105 and severe OSA in 303 patients according to their Apnea Hypopnea Index (AHI). In 139 individuals, AHI was <5/h and they were served as control group. Mean number of comorbidities increased with OSA severity (1.5±1.3 in mild, 1.7±1.4 in moderate, and 1.8±1.6 in severe OSA; P=0.048). Among OSA patients, female patients were older (56.2±10.9 vs. 52.8±13.3 years, P=0.001) and more obese [body mass index (BMI) 36±8.7 vs. 32.9±5.9 kg/m(2), P<0.001]. A significantly higher total number of comorbidities (2.3±1.6 vs. 1.6±1.4; P<0.001) was observed in female patients in comparison with men. This difference was not observed in controls. Smoking prevalence (current or ex-smokers) was significantly higher in men (75% vs. 46.2%, chi-squared: 35.107, P<0.001). Females with OSA had a higher prevalence of comorbidities such as hypothyroidism (21.4% vs. 2.9%, chi-squared: 48.145, P<0.001), depression (13.7% vs. 1.9%; chi-squared: 29.239; P<0.001), arterial hypertension (58.1% vs. 45.7%; chi-squared: 5.677; P=0.021) and heart failure (6% vs. 1.7%; chi-squared: 6.490; P=0.019) in comparison with male patients. CONCLUSIONS: Women with newly diagnosed OSA are older and more obese, with higher burden of comorbidities than men. Hypothyroidism, depression, arterial hypertension and heart failure are more prevalent in women with OSA than in men.